Economic geography of the USSR; : general information, geography of the industry, agriculture and transport - Lavrishchev, A. N. (Alekseĭ Nikitich); Myshne, David (Moscow: Progress Publishers, 1969)
De Russische economie en geografie uitgelegd in een lijvig boek aan de hand van tekst, tabellen, kaarten, foto's, ...
Keywords: Soviet Union -- Economic conditions -- 1955-1965.